Ten Reasons Why People With Down Syndrome are Protected From the Development of Most Solid Tumors -A Review - Osuna-Marco, Marta Pilar; López-Barahona, Mónica; López-Ibor, Blanca; Tejera, Águeda Mercedes (Frontiers in Genetics, 2021)
People with Down syndrome have unique characteristics as a result of the presence of an extra chromosome 21. Regarding cancer, they present a unique pattern of tumors, which has not been fully explained to date. Globally, people with Down syndrome have a similar lifetime risk of developing cancer compared to the general population. However, they have a very increased risk of developing certain tumors (e.g. acute leukemia, germ cell tumors, testicular tumors and retinoblastoma) and, on the contrary, there are some other tumors which appear only exceptionally in this syndrome (e.g. breast cancer, prostate cancer, medulloblastoma, neuroblastoma and Wilms tumor). Various hypotheses have been developed to explain this situation. The genetic imbalance secondary to the presence of an extra chromosome 21 has molecular consequences at several levels, not only in chromosome 21 but also throughout the genome. In this review, we discuss the different proposed mechanisms that protect individuals with trisomy 21 from developing solid tumors: genetic dosage effect, tumor suppressor genes overexpression, disturbed metabolism, impaired neurogenesis and angiogenesis, increased apoptosis, immune system dysregulation, epigenetic aberrations and the effect of different microRNAs, among others. More research into the molecular pathways involved in this unique pattern of malignancies is still needed.